Estado nutricional e alterações metabólicas de pessoas vivendo com HIV/AIDS em atendimento ambulatorial em um hospital de referência de Belém-PA - GUERRA, Evelyn Letícia Neves (2024)
To identify the nutritional status and the emergence of metabolic changes in people living with HIV/AIDS. Methods: This is a cross-sectional study that was carried out with 95 patients living with HIV/AIDS aged 20 to 63 years. The variables used included: clinical diagnosis, sex, age, behavioral variables, anthropometric measurements and biochemical tests. From this, the collected data were analyzed using the BioEstat 5.0 software. The Kolmogorov-Smirnov normality tests and Kruskal-Wallis analysis of variance were used, considering a significance level of 5% with p value < 0.05.Utilizou-se os testes de normalidade de Kolmogorov-Smirnov e Shapiro-Wilk, a análise de variância pelo teste t de amostras independentes e Teste de correlação de Pearson, considerando um nível de significância de 5% com p valor < 0,05. Results: 95 patients were analyzed, there were a greater number of women at risk of metabolic complications than men based on waist circumference. According to the body mass index, women presented higher levels of grade 1 obesity, while the majority of male patients were overweight. The tests indicated glycemic alterations present among the patients, the clinical diagnosis demonstrated a family history of morbidities and the practice of physical activity was adhered to by 38% of the patients. Conclusion: it is concluded that the study data demonstrated risk factors for the development of metabolic changes in these patients.